Overcoming the Challenges of Nepotism to Create a System Fair and Transparent Selection in Business Entities Regional Property in North Sumatra - Nurul Huda Chasanah; Muhammad Syahrizal Nasution; Debora Tifani Turnip; Ritha F. Dalimunthe; Prihantin Lumbanraja (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
The practice of nepotism in the employee selection process at Regional Owned Enterprises (BUMD) in North Sumatra, which has an impact on transparency, fairness and organizational effectiveness. BUMDs have an important role in regional economic development, but nepotism practices often damage the integrity of the recruitment process. Through a qualitative approach and case studies, this research reveals that nepotism creates inequality in employee selection, reduces the quality of human resources, and reduces public trust in BUMD. This article also identifies the factors that cause nepotism and offers solutions in the form of selection transparency, anti-nepotism policies, independent supervision, and outreach to build a culture of meritocracy in BUMD. By overcoming nepotism, BUMD is expected to be able to create a fair and professional recruitment system, thereby supporting the achievement of optimal performance.